Contribution of TARDBP mutations to sporadic amyotrophic lateral sclerosis. Issue 2 (17th October 2008) - Daoud, H; Valdmanis, P N; Kabashi, E; Dion, P; Dupré, N; Camu, W; Meininger, V; Rouleau, G A
Abstract : Aims and background: Mutations in the TARDBP gene, which encodes the TAR DNA binding protein (TDP-43), have been described in individuals with familial and sporadic amyotrophic lateral sclerosis (ALS). We screened the TARDBP gene in 285 French sporadic ALS patients to assess the frequency of TARDBP mutations in ALS. Results: Six individuals had potentially deleterious mutations of which three were novel including a Y374X truncating mutation and P363A and A382P missense mutations. This suggests that TARDBP mutations may predispose to ALS in approximately 2% of the individuals followed in this study. Conclusion: Our findings, combined with those from other collections, brings the total number of mutations in unrelated ALS patients to 17, further suggesting that mutations in the TARDBP gene have an important role in the pathogenesis of ALS.